The main features of the development of the toll road model in the republic of Azerbaijan - Oghlu Aslanov, Emin Shahin (Dunakavics, 2024)
The article examines the role of toll road services in the development of the national economy of the Republic of Azerbaijan. Conducted analyses suggest that the implementation of paid services in road infrastructure development is considered necessary. It should be noted that the funds collected for toll road services may lead to a reduction in state budget expenditures allocated to this area. In most foreign countries, the use of paid transportation services is considered economically viable. The article also identifies the positive impact of the toll road model on national economic sectors.